Peru : Request for an Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Peru. - International Monetary Fund. Western Hemisphere Dept.. (Washington, D.C. : International Monetary Fund, 2022)
Over the last quarter of a century, Peru has become one of the most dynamic economies in Latin America. During this period, Peru built very strong policy and institutional frameworks and economic fundamentals while maintaining external, financial, and fiscal stability. The strength of the Peruvian economy was tested with the COVID-19 pandemic in 2020, when the economy collapsed, leading to a significant deterioration of the fiscal accounts. Subsequently, the economy recovered strongly in 2021, and the fiscal position strengthened considerably, while inflationary pressures emerged (in line with global trends). However, Peru is bearing a very high humanitarian and economic cost from the COVID-19 pandemic, sizable under-employment, and a large increase in poverty. These challenges and recent social unrest related to high energy and food prices point to the need to accelerate structural reforms to foster high and inclusive growth. While political uncertainty has risen, with frequent cabinet reshufflings, the authorities remain committed to maintaining their very strong policy frameworks and prudent macroeconomic policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Peru